Quality of Life Is Not Deteriorated After Extrapleural Pneumonectomy vs. (Extended) Pleurectomy/Decortication in Patients With Malignant Pleural Mesothelioma - Lauk, Olivia; Patella, Miriam; Neuer, Thomas; Inci, Ilhan; Weder, Walter; Opitz, Isabelle (Frontiers in Surgery, 2021)
Background Extrapleural pneumonectomy (EPP) for malignant pleural mesothelioma (MPM) is more and more abandoned due to high morbidity and mortality rates and impaired Quality of Life (QoL). However, there are still rare indications for this intervention. The aim of the present longitudinal prospective study was to monitor QoL and lung function in patients undergoing EPP and compare the outcomes with extended pleurectomy/decortication ((E)PD). Methods Between June 2013 and June 2017 42 patients underwent induction chemotherapy followed by either EPP (n=7) or (E)PD (n=35). All patients filled out the EORTC QLC-C15-PAL, –LC13, and SF-36 self-rating questionnaires preoperatively, six weeks and four months after the operation. Additionally, lung function was measured preoperatively and four months postoperatively. Results We observed no significant differences in all QoL-categories (general global health, pain, and dyspnea) between both surgical procedures, over the whole observation period. Moreover, a general tendency towards restoration of the preoperative QoL status was documented at four months after both operations. Forced expiratory volume in 1 second (FEV1) showed a significant decrease after surgery in both groups (EPP group p=0.06, (E)PD group p <0.001); also, the forced volume vital capacity (FVC); significantly decreased (EPP group p=0.046 P/D group <0.001). Diffusion capacity did not show significant changes. Conclusion According to our results, QoL is not longer severely impaired after EPP compared to EPD and should therefore not be used as an argument against EPP in principle. However, indication has to be carefully evaluated for each patient.